Design and construction of magnetic flux leakage inspection system for ferromagnetic material - Wong, Toh Ming (2004)
The purpose of this study is to develop a magnetic flux leakage inspection system for ferromagnetic materials. It features a newly designed scanner, together with its signal processing circuit and software: Strong permanent magnet discs (1Tesla) are used to establish a magnetic flux in the material to be inspected. When there is no defect, the uniform flux remains in the plate. In contrast, flux leakage occurs outside the plate when there is a local defect due to corrosion or erosion. Hall effect sensor which can detect thls flux leakage is placed between the poles of the magnet and generate an electric signal proportional to the magnetic leakage flux. Defects causing a leakage flux exceedmg an adjustable predetermined threshold are detected and can be recorded. The amount of leakage flux is dependent on depth, width, breadth of the defects, and also the lie-off sensor and the plate thickness. The developed system enables fast scanning of ferromagnetic plate with qualitative results, with optimum speed 0.2-0.7ms-1. Its sensitivity is 0.2V(mT) -1 and it is able to resolve to defects as close as lrnrn apart. From the output signal displayed on the computer, the location and the severity of defects can be determined